Formalização de workflow nets utilizando lógica linear: análise qualitativa e quantitativa - Passos, Lígia Maria Soares (2009)
This work presents a method for qualitative and quantitative analysis of WorkFlow nets based on the proof trees of linear logic, and an approach for the verification of workflow specifications in UML through the transformation of UML Activity Diagrams into WorkFlow nets. The qualitative analysis is concerned with the proof of soundness correctness criterion defined for WorkFlow nets. The quantitative analysis is based on the computation of symbolic dates for the planning of resources used to handle each task of the workflow process modeled by a t-Time WorkFlow net. For the verification of the specifications of workflow processes mapped into UML Activity Diagrams are presented formal rules to transform this ones into WorkFlow nets. In this context is proposed the analysis and correction of critical points in UML Activity Diagrams through the analysis of proof trees of linear logic. The advantages of such an approach are diverse. The fact of working with linear logic permits one to prove the correctness criterion soundness in a linear time without considering the construction of the reachability graph, considering the proper structure of the WorkFlow net instead of considering the corresponding automata. Moreover, the computation of symbolic dates for the execution of each task mapped into the t-Time WorkFlow net permits to plan the utilization of the resources involved in the activities of the workflow process, through formulas that can be used for any case handled by the correspondent workflow process, without to examine again the process to recalculate, for each new case, the dates of start and conclusion for the activities involved in the process. Regarding the verification of workflow processes mapped into UML Activity Diagrams, the major advantage of this approach is the transformation of a semi-formal model into a formal model, such that some properties, like soundness, can be formally verified.